P004: What happens to cognitive load during trauma skill training using computer based video instructions?. (2nd June 2016) - Addison, R.N.; Rohr, L.E.; Dubrowski, A.
Abstract : Introduction: In the clinical settings, emergency physicians are faced with situations that require multitasking such as interacting with other team members, documentation and utilization of computer resources whiles ensuring competency on a particular trauma skill. The purpose of this study was to assess the effect of multitasking on cognitive load when learning a common trauma skill.Methods: Sixteen students who had no previous experience with the one-handed square knot were randomly assigned to one of the two groups: practice and non-practice groups. A pre-recorded instructional video of a one-hand knot tying was presented to all participants. Next, the practice group completed a single session of 10 trials of the one-hand knot tying using a benchtop simulator, while the non-practice group did not. All returned a week later for a transfer task on a different simulator. On trials 1, 4, 7, 10 and during the transfer performance the participants performed under dual task conditions, where they were asked to focus on the knot-tying task, but also to react as fast as possible to the illumination of an incandescent light bulb by pressing a foot pedal. Subjective ratings of mental effort, and reaction time to the visual stimulus were used as indices of cognitive load.Results: A repeated measure ANOVA showed a significant effect of dual task on subjective measure of mental effort ( F (4, 28) = 10.35, p = .001, ω = .60) and reaction time ( F (4, 28) = 7.93, p = .001, ω = .53), with plots indicating cognitive load plateaued by the 7 th trial.Conclusion: These findings highlights the number of trials necessary to attain a level of proficiency in a basic trauma skill such as the one-hand knot tying, ease the level of cognitive load and possibly enhance transfer to more challenging tasks.